DEVELOPMENT OF CHARACTER EDUCATION IN ELEMENTARY SCHOOL THROUGH MACROMEDIA FLASH FOKLORE - Suprani Suprani; Nana Hendracipta (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract. This study aims to describe the development of character education in elementary schools through macromedia flash folklore. Character education that has been implemented in 2013 curriculum in schools at Indonesia that give influence to all. This research uses descriptive qualitative research. The data took from elementary school students used interview, observation, and focus discussion techniques. Character education is also called as moral education, which aims to form good morals. The character education process in elementary schools must be adjusted to the development of the age of their students, the media used is macromedia flash of folklore which contains many character values accompanied by exemplary, directional, courageous, continuous reminders, repetitions or organizational exercises and ‘qolbu’ (heart).Keywords:character education, folkloe, elementary School